imagens do sagrado para os dependentes químicos - Oton, Karla Muniz Barreto (2015)
In the course of time, psychoactive substances is used in the treatment of some diseases, so asstimulants and in the devotion to the sacred; today, the reasons for the use of drugs have been quite diversified and drug addiction is becoming a matter of concern for Brazilian society. The religious phenomenon and spirituality have contributed significantly in prevention and recovery from drug addiction, as well as public theology has collaborated in the process of prevention and social care, along with treatment centers and faith based therapeutics communities. This thesis presents the results of a survey, which main objective was to identify the sacred images to young people between 18 and 35 who are in the recovery process in domestic in the Manasseh Project, who for more than 20 years is working with treatment programs in 21 states of Brazil. As theoretical framework, we base on Durand's Theory of the Imaginary, which identifies imaginary structures and mystical data, thus configuring the image of the sacred, what contributes to enhance the recovery process of the drug addicted. The mystic data, were analyzed by the Nine Elements Test, (AT-9 by Yves Durand). The analysis identified the images that reflect heroism, protection, and hope in the divine intervention in the process de drug addiction recovery, that once internalized , lead towards a practical faith in the supernatural, acting in the will and in the character of the man who is found dehumanized by the addiction. In the discourse about spirituality, we conclude that the image elements showed the faith, the church and the Word of God as predominant factors to face overall process of treatment in recovering from addiction.